Multicriteria analysis to select team members for software projects (Research, Society and Development, 2020)
This study presents an application of Multicriteria Analysis for evaluation and selection of members of software project teams through the adequacy of the technical profile, aiming to verify if existing teams used technical criteria for their composition. It uses documentary self-assessment of knowledge made by employees, field survey to define required levels of knowledge in projects and weighting through peer-to-peer comparison using AHP, categorization of knowledge using context analysis and calculation of average technical adequacy indexes (TAI), using both qualitative and quantitative approaches. It explores a new application of the AHP method that aims to improve decision making in selection of team members for software development. As main results found that there was a low level of technical adequacy in the analyzed projects (less than 50%). Corroborating this result, simulation of the redistribution of members between teams caused absolute improvement of 2.3% and relative improvement of 10% in indicator. This result indicated that technical criteria is not the one adopted in selection of team members or there were restrictions at choice. This study shows that is possible to use the AHP method to support decision making when selecting team members using technical criteria, increasing assertiveness.